The facial effects of tooth wear rehabilitation as measured by 3D stereophotogrammetry. (June 2018) - Sterenborg, Bernadette A.M.M.; Maal, Thomas J.J.; Vreeken, Rinaldo; Loomans, Bas A.C.; Huysmans, Marie-Charlotte D.N.J.M.
Abstract: Objective: Evaluate the effect of a full rehabilitation, including an increase of vertical dimension of occlusion (VDO), in patients with severe tooth wear on changes in facial appearance. Methods: Patients with severe tooth wear were restoratively treated using direct composite restorations, including an increase of the VDO. Before and one month after treatment 3D stereophotographs were taken and facial changes were measured with the use of 3D cephalometric landmarks. Cast models were used to determine the Tooth Wear Index (TWI) and the VDO-increase. The Orofacial Esthetic Scale-questionnaire was used to evaluate subjective happiness with appearance. Paired Student's t -tests were used to evaluate the changes after full rehabilitation. The relation between the facial changes, VDO-increment and TWI-score were analyzed using multiple regression models (p < 0.05). Results: 44 Patients (35 men, 9 women, mean age: 38.2 ± 7.1 y) participated in this study. Mean TWI-score at baseline was 3.3 ± 0.5 and the mean increase in VDO was 1.6 ± 0.9 mm. Lower face height increased by 1.9 mm (p ≤ 0.001). Patients reported a significant improvement in orofacial appearance: OES-summary score of 34.3 ± 11.2 before and 59.9 ± 6.8 one month after treatment (p < 0.001). The increase of VDO resulted in an increase in Lower Face Height (p ≤ 0.002), whereas the TWI-score at baseline had no effect on the facial changes. The applied increase in VDO and TWI-score were not related to changes in OES-scores. Conclusions: A full rehabilitation with an increase in VDO resulted in objective differences in facial height as measured with 3D stereophotogrammetry. Clinical significance: In patients with severe tooth wear, receiving a full rehabilitation including an increase in vertical dimension of occlusion, an objectively change will occur in the Lower facial height, but this effect will be subjectively judged as a positive change.